The Violation of Maxims and The Conversational Implicature in The Movie Entitled â€œHichki 2018â€ - Hendra Efendi (Jurnal Penelitian Mahasiswa Indonesia, 2023)
The Violation of maxims and the conversational implicature are common to happen in everyday conversations, movies, songs, etc. This research aims to analyze and describe the violation of the maxim and the conversational implicature in the movie entitled â€œHichki 2018â€. This qualitative study employs a close-reading method. The data are classified using plot segmentation and they are in the form of utterances in the movie that contain maxims violations and conversational Implicature. Data collection is done by downloading the film and its script, watching the film then, collecting data from the script. Data analysis is done by compiling data, analyzing data by using Griceâ€™s theory, and writing the conclusion. The result of this research shows that there are twenty-seven totals of all analyzed utterances. there are three violations of maxims found including the maxim quantity in total number is one, the maxim of relevance in total number is one, and the maxim of manner in total number is three. The Conversational Implicature is found outside of the violation of maxim in five utterances. The violation of maxims in this movie gives a deeper meaning to the audience which makes this story more dramatic through the dialogue contained in it.